FRI0136 Immune adsorption in highly active sle increases the risk of bacterial, but not of severe viral infections. (1st June 2001) - Stummvoll, GH; Aringer, M; Jansen, M; Goldammer, A; Derfler, K; Smolen, JS; Graninger, WB
Abstract : Background: Active SLE patients undergoing plasmapheresis and cyclophosphamid therapy are at high risk of severe bacterial and viral infections. Immune adsorption (IAS) is a more novel approach to autoantibody removal with an unclear risk of infections in SLE. Objectives: We therefore decided to investigate the risk of infections in patients undergoing longterm IAS. Methods: We analysed the records of ten consecutive active SLE patients treated with long term IAS (mean 38 months) for the occurrence of severe infectious disease. We compared the IAS patients to historical control groups 1 of 9 patients under plasmapheresis and cyclophosphamid (PP) and 12 patients treated with cyclophosphamid (CX) alone for similar time periods. Results: One IAS patient died from gram-negative septicemia. Three localised bacterial infections (two gram-positive, one gram-negative) were treated with antibiotics. All infections occurred in the subgroup of five highly active patients (SIS >15, mean 17.7 ± 0.9) who all underwent additional CX therapy, showing characteristics similar to the CX and PP control groups (SIS 18.7 ± 2.4 and 20.3 ± 3.7, respectively). Bacterial infections were more frequent than in the CX group (4/5 vs 1/12, p < 0.01), but similar to the PP group. No severe viral infections were detected. Conclusion: IAS did not promote severe viral infections, but was associated with an increased rate of potentially life-threatening bacterial infections in SLE patients with very active disease. Reference: Aringer M, Smolen JS, Graninger WB. Severe infections in plasmapheresis-treated systemic lupus erythematosus. Arthritis Rheum. 1998;41(3):414–20